1995
DOI: 10.1007/bf02349636
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of submucosal invasive colorectal carcinoma with special reference to risk factors for lymph node metastasis

Abstract: A clinicopathological analysis of the risk factors for lymph node metastasis was performed in 177 patients with submucosal invasive colorectal carcinoma (CRC). The submucosal deepest invasive portion was histologically subclassified as well (W), moderately (M), or poorly (Por) differentiated. M type was further subdivided into moderately-well (Mw) and moderately-poorly (Mp) differentiated. The pattern of tumor growth was classified as polypoid growth (PG) and non-polypoid growth (NPG). Lymph node metastasis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
119
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 25 publications
7
119
1
Order By: Relevance
“…According to previous reports, moderately or poorly differentiated adenocarcinoma 3,7,12,13 , and a bud-like structure 9 in submucosal invasive areas are risk factors for lymph node metastasis. Although our data trends were similar, these factors did not show statistical significance in our study.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…According to previous reports, moderately or poorly differentiated adenocarcinoma 3,7,12,13 , and a bud-like structure 9 in submucosal invasive areas are risk factors for lymph node metastasis. Although our data trends were similar, these factors did not show statistical significance in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Although our data trends were similar, these factors did not show statistical significance in our study. Moreover, many investigators [3][4][5][6][7][8][9][10][11][12][13][14][15] list mucinous adenocarcinoma as a Risk of metastasis of submucosal colon cancer Y Egashira et al risk factor for lymph node metastasis. In this study, mucinous adenocarcinoma was considered as two types, one composed of undifferentiated nontubular carcinoma (signet ring cell carcinoma in the majority) and one composed of differentiated tubular adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the number of cases of ER for early colorectal carcinoma has increased. However, reviews of the literature showed that lymph node metastasis occurred in approximately 10% of the patients with submucosal invasive colorectal carcinoma (Tanaka et al 1995;Suzuki et al 2003). Lymph node metastasis is one of the most important prognostic factors in colorectal carcinoma (Eisenberg et al 1982;Gennari et al 2000).…”
mentioning
confidence: 99%